The Impact of an Explanation Capability for a Computer Consultation System - Erdman, H. P. (Methods of Information in Medicine, 1985)
The impact of a computer consultation program including explanations for its decisions was examined. The consultation program was designed as a decision aid for non-psychiatrists regarding the treatment of depression. Both psychiatrists and non-psychiatrists were used to evaluate the system, with different results for the two groups. Explanations improved the non-psychiatrists’ attitudes towards the computer recommendations, while for psychiatrists the impact of explanation depended on the specific content of the recommendations and explanations. The results for psychiatrists were consistent with the view that explanations are important for computer consultation systems because they may help physicians decide whether or not the computer’s advice is reasonable.
Keywords: Computer Consultation Systems; Expert Systems; Explanation; Medical Decision Making